Comparison of the Reproductive Outcome Between 2 and 4 mg Daily Doses of Estradiol After Hysteroscopic Adhesiolysis: A Propensity Score Matching Analysis–Retrospective Cohort Study - Qiu, Dan-Er; Zhang, Wan-Lin; Liu, Jin; Yang, Fang; Miao, Ye; Tong, Ya-Fei; Xiao, Xi-Feng; Wang, Xiao-Hong (Frontiers in Endocrinology, 2022)
Objective: To investigate the effect of two postoperative doses of estradiol valerate (2 mg/d and 4 mg/d) on reproductive outcomes in patients with moderate to severe intrauterine adhesions (IUAs). Methods: A retrospective cohort study was conducted at a single tertiary reproductive medical center between January 2018 and December 2019 to compare the reproductive outcomes of two doses of estradiol valerate (2 mg and 4 mg daily) after hysteroscopic adhesiolysis. All patients received adjuvant postoperative treatment with a Foley catheter, hyaluronic acid gel, and medication therapy. Hysteroscopy was repeated every 7 days after surgery. Multivariate regression analysis and propensity score matching (PSM) were performed to minimize intrinsic bias. Results: A total of 212 patients with moderate to severe IUAs were included: 74 patients received 2 mg estradiol valerate daily and 138 patients received 4 mg estradiol daily postoperatively. No significant differences were found in the reproductive outcomes between the two groups, including clinical pregnancy rates. The multivariable regression analyses both before and after PSM also showed that there was no significant difference in the menstrual improvement and clinical pregnancy rates between the two groups. Conclusions: We suggest the use of a lower dose (2 mg/d) of estradiol valerate as an adjuvant therapy for IUAs to minimize estrogen-related side effects.